2005
DOI: 10.1016/j.neuron.2005.01.043
|View full text |Cite
|
Sign up to set email alerts
|

GDNF and GFRα1 Promote Differentiation and Tangential Migration of Cortical GABAergic Neurons

Abstract: Cortical GABAergic neurons are generated in the ventral telencephalon and migrate dorsally into the cortex following a tangential path. GDNF signaling via GFRalpha1 was found to promote the differentiation of ventral precursors into GABAergic cells, enhancing their neuronal morphology and motility. GDNF stimulated axonal growth in cortical GABAergic neurons and acted as a potent chemoattractant of GABAergic cells. These effects required GFRalpha1 but neither RET nor NCAM, the two transmembrane signaling recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(175 citation statements)
references
References 63 publications
12
163
0
Order By: Relevance
“…Recently, ErbB/neuregulin signaling has been implicated in supporting migration through the LGE toward the cerebral cortex (22,23,56). Glial cell line-derived neurotrophic factor signaling via GFR␣1 has a role in the differentiation and migration of cortical GABAergic cells from the MGE (57). Likewise, chemorepellant tissues and factors have been identified that participate in directing these migrations (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ErbB/neuregulin signaling has been implicated in supporting migration through the LGE toward the cerebral cortex (22,23,56). Glial cell line-derived neurotrophic factor signaling via GFR␣1 has a role in the differentiation and migration of cortical GABAergic cells from the MGE (57). Likewise, chemorepellant tissues and factors have been identified that participate in directing these migrations (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…Steps that have been proposed include repulsion from the ganglionic eminences by an as-yet-unidentified factor (Marín et al, 2003), avoidance of the striatum by semaphorinmediated repulsion (Marín et al, 2001), and attraction to the cortex by neuregulins (Flames et al, 2004), GDNF (glial cell linederived neurotrophic factor) (Pozas and Ibanez, 2005), and HGF (hepatocyte growth factor) (Powell et al, 2001), but it has remained unclear why this complex framework is required.…”
Section: Why Have Interneuron Migratory Streams?mentioning
confidence: 99%
“…This activation decreases NCAM-dependent cell adhesion, illustrating a general principal that an optimal level of cell-substratum contact is needed for motility, with too much or too little impeding it. NCAM also mediates chemo-attraction of olfactory interneuron precursors to GDNF in the rostral migratory stream, but is not required for GDNF/GFRα1-mediated tangential migration of cortical interneurons [29].…”
Section: Ncam Signaling and Post-translational Modificationmentioning
confidence: 99%